2012
DOI: 10.1007/s10661-012-2777-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals in water samples and tissues of edible fish species from Awassa and Koka Rift Valley Lakes, Ethiopia

Abstract: The Ethiopian Rift Valley Lakes host populations of edible fish species including Oreochromis niloticus, Labeobarbus intermedius and Clarias gariepinus, which are harvested also in other tropical countries. We investigated the occurrence of six heavy metals in tissues of these fish species as well as in the waters of Lake Koka and Lake Awassa. Both lakes are affected by industrial effluents in their catchments, making them ideal study sites. Mercury concentrations were very low in the water samples, but concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
35
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 51 publications
15
35
2
Order By: Relevance
“…In comparison among metals studied in this creek water, Cr concentrations were highest in the water samples. Similar finding was reported in Awassa and Koka Rift Valley Lakes, Ethiopia (Dsikowitzky et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…In comparison among metals studied in this creek water, Cr concentrations were highest in the water samples. Similar finding was reported in Awassa and Koka Rift Valley Lakes, Ethiopia (Dsikowitzky et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Because of the feeding behavior of whitemouth croaker, these results suggest some degree of biomagnification for these elements, a phenomenon already observed with Hg in a previous study in the area (VIANA et al, 2005) and in other aquatic ecosystems (KEHRIG et al, 2007). Mercury biomagnification and bioaccumulation in fish depend mostly on the fish's position in the food web and its feeding habits (DSIKOWITZKY et al, 2013). However, As showed contradictory results in the literature in terms of the biomagnification process (DSIKOWITZKY et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
“…The reproductive status can affect the concentration of metals in the liver (MONSEFRAD et al, 2012). Although VIANA et al (2005) found similar relationships for M. furnieri in this region, it has not been possible to determine the reason for these results (MONSEFRAD et al, 2012;DSIKOWITZKY et al, 2013). More studies of the biomagnification and bioaccumulation processes of metals and metalloids are necessary, considering the importance of both species for the ecosystem and the fisheries.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Others focus on the heavy metals and organochlorine pesticides present in fish species, sediment and water samples, and the correlations between them (Nigussie et al 2010;Dsikowitzky et al 2012;Yohannes et al 2014). These studies detected e.g.…”
Section: Introductionmentioning
confidence: 99%